Product and Process Innovation and the Decision to Export: Firm-level Evidence for Belgium - Ilke Van Beveren; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
Using data from the Community Innovation Survey for Belgium in two consecutive periods, this paper explores the relationship between firm-level innovation activities and the propensity to start exporting. To measure innovation, we include indicators of both innovative effort (R&D activities) as well as innovative output (product and process innovation). Our results suggest that the combination of product and process innovation, rather than either of the two in isolation, increases a firm's probability to enter the export market. After controlling for potential endogeneity of the innovation activities, only firms with a sufficiently high probability to start exporting engage in product and process innovation prior to their entry on the export market, pointing to the importance of self-selection into innovation.
Keywords: D24; F14; L25; O31; O33; 330; Exports; Product innovation; Process innovation; Self-selection; Firm heterogeneity; Innovation; Betriebliche Forschung; Exportindustrie; Industrie; Belgien